X-Ray microtomography imaging of red lentil puffed snacks: Processing conditions, microstructure and texture. (February 2021) - Guillermic, R.-M.; Aksoy, E.C.; Aritan, S.; Erkinbaev, C.; Paliwal, J.; Koksel, F.
Graphical abstract: Highlights: Red lentil extrudates microstructure was characterized using X-ray microtomography. Number of separated cells, mean cell size and wall thickness were extracted. Microstructure depends on the extrusion conditions, and affects texture. Higher nitrogen injection pressure resulted in higher number of separated cells. Hardness is negatively correlated with the mean cell size and wall thickness heterogeneity. Abstract: Red lentils have a great potential to be used as healthy ingredients in puffed snacks due to their excellent nutritional qualities. However, these types of ingredients with relatively higher protein and fiber content when compared to ingredients that are typically used for the manufacture of puffed foods (e.g., refined cereal flours/starches) result in inferior textural quality. Extrusion processing parameters such as screw speed, moisture content and injection pressure of a blowing agent can be manipulated to optimize the microstructure of an extrudate, and as a consequence the texture of the final puffed product. In this study, X-Ray microtomography imaging is used to characterize and quantify the detailed microstructure of red lentil extrudates. The results indicate that an increase in the injected pressure of the physical blowing agent could be correlated with a decrease in mean cell size and wall thickness, as well as an increase in the number of cells. Evidence of wall rupture with an increased screw speed is also visible, and that effect can be counterbalanced by a higher moisture content during processing. A large variation of the cell wall thickness inside an extrudate (which can induce a weaker cellular structure) as well as a larger cell size and higher amount of wall rupture, significantly reduce the hardness of extrudates. This novel effort to quantitatively characterize the microstructure of red lentil extrudates using X-Ray microtomography establishes that an optimal product texture could, in principle, be achieved by manipulating extrusion parameters to achieve the perfect snack texture.